ORGANIZATIONAL AND PEDAGOGICAL SUPPORT OF THE PROCESS OF FORMATION OF STUDENTS’ SPIRITUAL VALUES IN INSTITUTIONS OF HIGHER EDUCATION - Lappo, Violetta (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The theoretical generalization and scientific solution of the problem of formation of students’ spiritual values in the educational process of an institution of higher education have been implemented in the article. Based on analysis of scientific sources in philosophy, psychology, pedagogy, the theoretical and methodological principles of formation of the individual’s spiritual values are substantiated. The purpose and objectives of the research is to determine the peculiarities of the organizational and pedagogical conditions of the process of formation of students’ spiritual values in the conditions of institutions of higher educational. To solve the research objectives, the following methods were used: analysis of philosophical, psychological, pedagogical literature; study of pedagogical experience; pedagogical experiment; generalization and systematization of empirical data on the research problem. The essence of the phenomenon “students’ spiritual values” is specified. The content of the structure of the individual’s spiritual values in the relation of cognitive, emotional and value, and praxical components is determined. The criteria and indicators, levels of formation of students’ spiritual values in institutions of higher education are determined and substantiated. The problem of diagnostics of the formation of individuals’ spiritual values during the period of their professional formation is characterized. Leading spiritual values are dignity, responsibility, tolerance, mercy, and self-sufficiency that are formed throughout education of youth in institutions of higher education. The author claims that it it is necessary to create comfortable conditions for the establishment and further self-improvement of each student’s personality in the educational environment of modern institutions of higher education. The potential of social and humanitarian disciplines and extracurricular activities of institutions of higher education regarding the formation of students’ spiritual values is revealed. The effectiveness of the organization and pedagogical conditions for the formation of students’ spiritual values in the educational process of institutions of higher education was developed, experimentally verified and proved: the construction of the spiritual-oriented content of students’ education; formation of an educational environment in the student group; individual support of the student regarding the expression of spiritual values. The indicators of the levels of the formation of students’ spiritual values in the experimental group at the control stage of the study significantly exceeded the indicators of the control group. These findings have confirmed the effectiveness of the author’s structural and functional model of the formation of students’ spiritual values in the educational process of the institution of higher education and the above-mentioned pedagogical conditions.